Arquitectura para nómadas modernos. Dinâmicas do Habitar Contemporâneo - Francisca Neto Soares de Moura (2016)
The period since the latter years of the 20th Century has been characterized by fast-paced technological evolution and globalization. This has created a more interconnected world and thus mobility (people, goods and services). Rapid changes in technology, politics and economics had an impact on housing dynamics as well. A continuously increasing amount of people who repeatedly move to another country or region for a variable period of time - the modern nomads - provides the motivation for this dissertation. Many mobile housing units have been designed in the past decade with human mobility in mind but reveal issues when incorporating the physical space in the design process and dealing with the social organization of space. The mobile condition of these projects is also questionable from a technical point of view, since self-sustainability and efficiency in relocation are hardly reconcilable. Therefore mobile architecture proves itself of little value as housing for modern nomads. The pursue of dwellings that are conscious of urban economy and ecology led to research on how to leverage the use of space, by seeking multifunctionality, reassessing conventional furniture and reevaluating boundaries between private and common space in shared and collective housing. In the New Media Age, the impact of a virtual dimension on people at a psychological, social and cultural levels and the change in the understanding of territorial identity set new ground for housing projects that take in consideration both individual and social conditions of one's use of space.